1996
DOI: 10.1046/j.1365-3083.1996.d01-2.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibodies from Patients with Primary Sjögren’s Syndrome and Systemic Lupus Erythematosus Recognize Multiple Epitopes on the La(SS‐B) Autoantigen Resembling Viral Protein Sequences

Abstract: The aim of this study was to investigate the epitope recognition pattern of La(SS-B) autoantibodies in sera from patients with Sjögren's syndrome (SS) and systemic lupus erythematosus (SLE) using overlapping synthetic decapeptides on solid phase. Eighty different decapeptides with five amino acids overlap from the human La(SS-B) autoantigen were synthesized on cellulose paper using F-moc chemistry. Tests were performed with 14 SS and six SLE sera. The results showed that the immune response to the La(SS-B) oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…The CMV-induced cell surface expression of the La autoantigen can then lead to the production of anti-La antibodies in genetically susceptible individuals. Another potential mechanism leading to the production of anti-La antibodies is the sequence homology of epitopes in the La protein with CMV antigens (molecular mimicry) [34,35]. The best evidence for this hypothesis is the presence of anti-La antibodies in the sera of patients with SS and SLE that cross-react with epitopes on CMV antigens [35].…”
Section: And Slementioning
confidence: 99%
“…The CMV-induced cell surface expression of the La autoantigen can then lead to the production of anti-La antibodies in genetically susceptible individuals. Another potential mechanism leading to the production of anti-La antibodies is the sequence homology of epitopes in the La protein with CMV antigens (molecular mimicry) [34,35]. The best evidence for this hypothesis is the presence of anti-La antibodies in the sera of patients with SS and SLE that cross-react with epitopes on CMV antigens [35].…”
Section: And Slementioning
confidence: 99%
“…Because they react with such antigens irrespective of species origin, and also human origin, they are conceptually defined as true autoantibodies. However, it is not established that the autologous antigens always account for their production, or whether such antibodies are induced as a consequence of stimulation with heterologous antigens mimicking autologous antigens (molecular mimicry, see for example references [1,2]), or complexes between autologous and heterologous antigens [3][4][5] or by other events that may contribute to, but not as a sole factor account for, increased antibody production, such as polyclonal B cell stimulation [6]. However, true autoantibodies may also be induced by autoimmune B-cells and T-cells, both recognizing determinants on single autoantigens or complexes of different autologous molecules, as indicated for antibodies to dsDNA by the pioneering results of Datta et al [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the sequences 145-164aa, 289-308aa, 301-320aa, and 349-364aa of La/SSB as well as 169-190aa and 211-232aa of Ro 60 kDa, have been extensively studied, exhibiting high sensitivity and specificity for autoantibody detection. [10][11][12][13] Early serological studies have shown positive associations of pSS with HLA-DR3, DR2, DR5, and DRw53. 14 15 Increased frequency of the haplotype HLA-DRB1*0301-DRB3*0101-DQA1*0501-DQB1*0201 has been found in Caucasoid patients with pSS, DRB1*0405-DRB4*0101-DQA1*0301-DQB1*0401 in Japanese patients, and DRB1*0803-DQA1*0103-DQB1*0601 in Chinese patients.…”
mentioning
confidence: 99%